Evaluation of Management Practices for Sustainability of Water Resources in Arror River Watershed, Kenya - Sang, C. C. (Africa Environmental Review Journal, 2022)
Water is an indispensable natural resource that is critical for sustaining life and ensuring healthy ecosystems. Since it is dynamic in nature with an ever-increasing demand, its sustainable use requires an integrated management approach. Impacts of water scarcity such as health problems, limiting economic and agricultural development and stress on ecosystems needs water resources to be managed sustainably. To understand this phenomenon, the study conducted sought to evaluate the various management practices for sustainable watershed and water resource management in Arror River watershed, Elgeyo Marakwet County. The primary data source was were remotely sensed data and socio-economic data while climate, river discharge and soil data formed the secondary data. Field surveys and questionnaires were used to collect information about indigenous and contemporary watershed management and conservation practices. GIS information was integrated with the Water Evaluation and Planning (WEAP) system and the Soil and Water Assessment Tool (SWAT, to analyse the various management practices in the watershed. The results from the field survey showed that the local communities in Arror river watershed had their traditional ways of managing water catchments with most respondents (89%) reporting the prohibition of cutting trees. They also reported some modern watershed management methods with agroforestry being the most popular (67.5%). Various scenarios were explored in both SWAT and WEAP models. The results from the SWAT model on the application of terracing and contour planting revealed a decrease in the annual mean flow of 15.4% and 24.1%, respectively while a combination of both revealed a reduction of 19.04%. The WEAP model scenarios revealed that the minimum ‘flow requirement’ scenario would yield the highest mean annual flows (85,113,000 m3 p.a) while the ‘irrigated agriculture increased’ scenario would yield the lowest mean annual flows over the 28 years (2013-2040). The ‘irrigated agriculture increased’ scenario posted the highest mean annual demand and the highest mean annual unmet demand. The ‘dam construction’ scenario revealed no unmet demand. The management practices that would enhance the sustainable management of the watershed include: contour farming, construction of a reservoir, maintenance of minimum environmental flows in the river, agroforestry and afforestation which are then recommended for Arror River watershed. Water managers and all stakeholders should understand how different drivers of change affect hydrology and therefore affect the related water demands and functions by the inhabitants in the basin so as to make informed decisions on the sustainable management of the watershed. The findings of this study are therefore intended to contribute towards sustainable watershed management.